Shifts in therapeutic practices and decline of medicinal cannabis in Indian North-Eastern Frontier (1826–1925) - Gita Bania (Journal of Cannabis Research, 2022)
Abstract Background The emergence of colonial medicine in the North-Eastern Frontier witnessed different phases of consistent competition and resistance. Herbs such as cannabis provided native physicians with a coherent power to resist colonial medical intervention. Before British rule, cannabis assumed great significance in the socio-economic, cultural, and religious spheres. The colonizers’ bioprospection of cannabis shifted the production and use of cannabis from a medical and recreational plant to an industrial and commercial commodity. British policies on cannabis caused its ban leading to natives’ reliance on colonial cannabis products. As a result, the native medical practitioners resisted for reviving cannabis in the indigenous therapeutics. This paper mainly aims to investigate the decline of medicinal cannabis in indigenous therapeutics, causing subtle resistance of the native physicians of the North-Eastern Frontier. Methods This paper follows a nomadology method based on primary and secondary sources to understand the impact on native physicians after the ban on private use, cultivation, and sale of cannabis. The primary sources/data have been collected from the Directorate of Archives: Government of Assam and Directorate of State Archives and Research Centre, Kolkata, West Bengal. Secondary sources have been collected from books, articles, and theses accessed from various libraries and websites. Results Ban on cannabis led to dual responses from the indigenous population of the frontier. First is the interest of the native physicians resisting the revival of cannabis in indigenous therapeutics. The second is the interest of the frontier’s elites, who viewed cannabis as a “dangerous drug.” The British policies of control and restrictions on cannabis, the rift of response from the natives, and the over-powering of the indigenous therapeutics by the colonial medical system led to the decline of medicinal uses of cannabis in the North-Eastern Frontier. Discussions Various pre-colonial and colonial factors helped colonial medical practices to get the upper hand over indigenous therapeutics. Such a shift led to the decline of indigenous medicinal cannabis causing native resistance, which was patient and silent. Conclusions British ban on cannabis resulted in a rift of native responses, resistance, and decline of cannabis in the indigenous therapeutics of the North-Eastern Frontier.